Biosynthesis of butyric acid by Clostridium tyrobutyricum. Issue 5 (28th May 2018) - Huang, Jin; Tang, Wan; Zhu, Shengquan; Du, Meini
ABSTRACT: Butyric acid (C3 H7 COOH) is an important chemical that is widely used in foodstuffs along with in the chemical and pharmaceutical industries. The bioproduction of butyric acid through large-scale fermentation has the potential to be more economical and efficient than petrochemical synthesis. In this paper, the metabolic pathways involved in the production of butyric acid from Clostridium tyrobutyricum using hexose and pentose as substrates are investigated, and approaches to enhance butyric acid production through genetic modification are discussed. Finally, bioreactor modifications (including fibrous bed bioreactor, inner disk-shaped matrix bioreactor, fibrous matrix packed in porous levitated sphere carriers), low-cost feedstocks, and special treatments (including continuous fermentation with cell recycling, extractive fermentation with solvent, using different artificial electron carriers) intended to improve the feasibility of commercial butyric acid bioproduction are summarized.